Photography in India
1 online resource (272 pages)
Keywords: Photography's prominence in the representation and experience of India in contemporary and historical times has not guaranteed it a position of sustained attention in research and scholarship. For a technology as all pervasive as photography, and a country as colossal as India, this scenario is somewhat of an anomaly. Photography in India explores elements of the past, present and future of photography in the context of India through speculation and reflection on photography as an artistic, documentary and everyday practice. The perspectives of writers, theorists, curators and artists are selectively brought to bear upon known as well as previously unseen photographic archives, together with changes in photographic practice that have been synchronous with contemporary India's rapid urban and rural transformation and the technological shift from chemistry and light to programming and algorithms. Essential reading for anyone interested in Indian photography, this book binds insights into a history of photography with its contemporary development, consolidating wide-ranging thinking on the topic and setting the agenda for future research.